550 An Axl-targeting monoclonal antibody that inhibits Axl activity and potently stimulates the innate immune response. (9th November 2020) - Alvarado, Diego; Vitale, Laura; Murphy, Mike; O'Neill, Thomas; Natoli, Edward; Lillquist, Jay; Crew, Linda; Wasiuk, Anna; Weidlick, Jeffrey; Sisson, Crystal; Widger, Jenifer; Mills-Chen, Laura; et al.
Abstract : Background: Axl is a member of the TAM (Tyro3/Axl/MerTK) family of receptor tyrosine kinases and a negative regulator of innate immunity. Activation of Axl through its ligand Gas6 leads to suppression of myeloid cell activity, while its activation in tumor cells drives tumor growth, metastasis, and is associated with acquired resistance to targeted therapies, radiotherapy and chemotherapy. Methods: Purified monoclonal antibodies and variants thereof were tested in human cancer lines and primary human myeloid cells for effects on Axl signaling and immune activation, respectively. Results: We describe a humanized IgG1 Axl-targeting monoclonal antibody (mAb), CDX-0168, that binds to the ligand-binding domain of Axl with sub-nanomolar affinity and potently inhibits Gas6 binding. In tumor cells, CDX-0168 inhibits Gas6-dependent Axl phosphorylation and signaling and elicits tumor cell killing via ADCC in vitro and in vivo. In primary human immune cells, CDX-0168 treatment induces potent release of pro-inflammatory cytokines and chemokines from dendritic cells, monocytes and macrophages through an Fc receptor-dependent mechanism and enhanced T cell activation in mixed lymphocyte reactions. Axl inhibition may further enhance antitumor activity associated with PD-(L)1 blockade. To this end, we generated a tetravalent bispecific Axl x PD-L1 antibody combining CDX-0168 with a potent anti-PD-L1 mAb (9H9) using an IgG-scFv format. The bispecific antibody elicits greater cytokine release and T cell activation in vitro than the combination of the parental antibodies, while maintaining robust Axl and PD-L1 blockade. Conclusions: Additional studies investigating simultaneous blockade of the Axl and PD-L1 pathways with other agents may further exploit the potential for this novel anti-cancer therapeutic approach.